Bacterial diversity and antibiotic resistance in water habitats: searching the links with the human microbiome - Ivone Vaz Moreira (2014)
Water is one of the most important bacterial habitats on Earth. As such, water represents also a major way of dissemination of bacteria between different environmental compartments. Human activities led to the creation of the so-called urban water cycle, comprising different sectors (waste, surface, drinking water), among which bacteria can hypothetically be exchanged. Therefore, bacteria can be mobilized between unclean water habitats (e. g. wastewater) and clean or pristine water environments (e. g. disinfected and spring drinking water) and eventually reach humans. In addition, bacteria can also transfer mobile genetic elements between different water types, other environments (e. g. soil) and humans. These processes may involve antibiotic resistant bacteria and antibiotic resistance genes. In this review, the hypothesis that some bacteria may share different water compartments and be also hosted by humans is discussed based on the comparison of the bacterial diversity in different types of water and with the human-associated microbiome. The role of such bacteria as potential disseminators of antibiotic resistance and the inference that currently only a small fraction of the clinically relevant antibiotic resistome may be known is discussed.